Position Description Analysis: A Method for Describing Academic Roles and Functions - Renner, K. Edward; Skibbens, Ronald J. (Canadian Journal of Higher Education, 1990)
Similar to the 1960s, higher education is once again in a period of rapid social chance in which new demands and expectations are being made on colleges and universities. This time, however, new money is not available for the transition to be achieved though additional growth. In this paper, the methodology of Position Description Analysis is presented using Dalhousie University as a case study. Position Description Analysis is a tool for assessing the discrepancy between the status quo and the specializations needed for colleges and universities to meet the new demands and expectations which are being made of them. It is concluded that there is a need for dramatic realignement of fields of specialization in order to shift from the emphases of the past to those of the future. However, because the faculty higher in the 1960s are now tenure, but no due to retire until after the year 2000, higher education must find internal strategies for chance or face externally imposed solution to their current lack of flexibility.